Analysis of Stress Events in Students of The Faculty of Public Health, Muhammadiyah University of Jakarta in Online Learning During The Covid19 Pandemic in 2021 - Ari Laras; Alifya Fitri Ananda; Alvi Fauzia; Astri Maretta; Munaya Fauziah (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
Online learning is a learning activity by utilizing the internet network, local area network as a method of interacting in learning such as delivering material. Stress in this study is defined as a condition experienced by a person when there is a mismatch between the demands received and the ability to overcome them. This research is qualitative research using the Rapid Assessment Procedure design. The selection of samples or informants uses the principle of appropriateness, selected by purposive method or determines the criteria for informants who can provide information following the research objectives. Online learning has several causes including lack of concentration due to environmental disturbances, unstable internet network, many assignments from lecturers, lack of communication or social interaction. Online learning for FKM UMJ students is influenced by: lack of concentration due to environmental disturbances, unstable internet network, many assignments from lecturers, lack of communication or social interaction. The way to deal with stressful events in online learning can be done by doing positive activities, looking for calm or refreshing, managing time well.